Implementation Of The Simple Additive Weighting (SAW) Method On The Determination Of Scholarship Recipients - Made Ary Sanjaya; I Gusti Arya Sidhi Narendra (TIERS Information Technology Journal, 2023)
In recent years, technology and science have developed quite drastically. With advances in technology and science, we can create a system to help solve a problem such as granting scholarships. The purpose of this research is to build a decision support system to help and make it easier to determine who is entitled to get a scholarship. The method we use here is Simple Additive Weighting (SAW) which simplifies the process of awarding scholarships which is then carried out by a process of ranking and determining the weight values for each criterion attribute to get the best alternative and who is entitled to get the scholarship. The data used to determine scholarship recipients includes GPA data (Grade Point Average), parents income data, and parents dependents data. The results obtained in this study indicate that a decision support system can make it easier to determine who is entitled to get the scholarship without requiring more time than the manual method which will also make it easier for humans to make decisions.